(untitled) - Sharpnack, Rayona (San Francisco, 2007)
Silicon Valley wunderkind Rayona Sharpnack has been a schoolteacher, tennis champion, manager and player for a women's professional softball team, and a celebrity who coaches some of the most successful leaders in business. Trade Up! draws on Sharpnack&'s experience, as well as stories of successful leaders she has worked with, to reveal how leaders limit themselves by holding on to ideas or assumptions about ourselves—what she calls your “context” —that are no longer valid. Trade Up! outlines the 5 steps to help leaders gain awareness of these assumptions and trade up from limiting beliefs and behaviors to those that will help them change the world
Keywords: Leadership,Success in business,Nghệ thuật lãnh đạo